Expression and in silico Analysis of CIDRα1 Recombinant Protein from Plasmodium Falciparum as a Malaria Subunit Vaccine Candidate - Sulistyaningsih, Erma; Istinaroh, Nurul; Dewi, Rosita; Hairrudin, Hairrudin (Trends in Sciences, 2022)
Malaria vaccination is an essential approach to combat malaria. One major protein studied for vaccine development is Plasmodium falciparum erythrocyte membrane protein-1 (PfEMP1). It contains several important domains for malaria pathogenesis. The binding of Cysteine-rich interdomain region α1 (CIDRα1) of PfEMP1 to endothelial protein C receptor (EPCR) is associated with cerebral malaria, while CIDRα1 binding to CD36 has been correlated with uncomplicated malaria. The vital function of CIDRα1 of PfEMP1 makes it a potential vaccine candidate to prevent clinical features of malaria. A long journey of vaccine development can be shortened by the advancement of bioinformatics and biotechnology techniques. This study aimed to express the recombinant CIDRα1 of PfEMP1 and investigate its potency as a malaria subunit vaccine candidate by in silico analysis. Constructed CIDRα1-PfEMP1 was expressed in E. coli BL21(DE3) after induction with Isopropyl ß-D-1-thiogalactopyranoside (IPTG) and purified using Ni-NTA column. In silico analysis on CIDRα1 of PfEMP1 sequence was conducted using ProtParam Tool for its physicochemical properties, Iterative Threading ASSEmbly Refinement (I-TASSER) server and JPred4 program to predict secondary structure, 3D modelling, and ligand-binding site, BepiPred 2.0 and Kolaskar-Tangaonkar to predict B-cell epitope, NetCTL server to determine T-cell epitope, and Vaxijen v2.0 server to predict its antigenicity. The chimeric CIDRα1 of PfEMP1 protein had a 27 kDa molecular weight and was classified as a stable protein. The secondary structure consisted of 6 helices connected with loops. It revealed similarity to CD36-binding protein, EPCR-binding domain, and protein involved in rosetting. The 3D structure modelling demonstrated conserved ligand-binding sites and accessible surface area, which are vital for receptor binding. It had B-cell and T-cell epitopes and was non-allergenic. The properties of the chimeric CIDRα of PfEMP1 indicated its potential as a malaria subunit vaccine candidate. HIGHLIGHTS The binding capacity of CIDRα1 of PfEMP1 to endothelial protein C receptor (EPCR) and CD36 makes it a potential vaccine candidate to prevent clinical malaria The chimeric CIDRα1 of PfEMP1 protein was a stable protein and showed similarity to CD36-binding protein, EPCR-binding domain, and protein involved in rosetting, which demonstrated conserved ligand-binding sites and accessible surface area, which are vital for receptor binding The chimeric CIDRα1 of PfEMP1 protein had B-cell and T-cell epitopes and was non-allergenic in in silico analysis, indicating its potential as a malaria vaccine candidate GRAPHICAL ABSTRACT